2004
DOI: 10.4049/jimmunol.173.3.2091
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Aspirin-Triggered Lipoxin A4 Analog Blocks Phosphorylation of Leukocyte-Specific Protein 1 in Human Neutrophils

Abstract: Lipoxins and their aspirin-triggered 15-epimers are endogenous anti-inflammatory agents that block neutrophil chemotaxis in vitro and inhibit neutrophil influx in several models of acute inflammation. In this study, we examined the effects of 15-epi-16-(p-fluoro)-phenoxy-lipoxin A4 methyl ester, an aspirin-triggered lipoxin A4-stable analog (ATLa), on the protein phosphorylation pattern of human neutrophils. Neutrophils stimulated with the chemoattractant fMLP were found to exhibit intense phosphorylation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Interestingly, another study showed that LL-37 stimulated p38 and LTB 4 formation in PMNs (34), although the signal transduction pathway leading to p38 activation was not elucidated. These findings, together with the data herein, suggest that the ability of SPMs to rapidly and transiently limit intracellular calcium and CaMKII-p38-MK2 signaling may be a fundamental mechanism for preventing excessive or prolonged inflammation (33,35).…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, another study showed that LL-37 stimulated p38 and LTB 4 formation in PMNs (34), although the signal transduction pathway leading to p38 activation was not elucidated. These findings, together with the data herein, suggest that the ability of SPMs to rapidly and transiently limit intracellular calcium and CaMKII-p38-MK2 signaling may be a fundamental mechanism for preventing excessive or prolonged inflammation (33,35).…”
Section: Discussionmentioning
confidence: 75%
“…Along these lines, using proteomic analysis, ATLa blocks phosphorylation and activation of leukocyte-specific protein-1 along with several other components of the p38 MAPK pathway in human PMNs. These results indicate a regulatory role for LXA 4 and ATL on the p38 MAPK cascade, which is known to promote chemotaxis and other inflammatory responses (Ohira et al, 2004).…”
Section: Fibroblast: Inhibition Of Proinflammatory Cytokinesmentioning
confidence: 82%
“…cAMP is also intrinsically involved in the regulation of cytoskeletal rearrangement and function (12). More recently, it was reported that neutrophils stimulated with the chemoattractant fMLP exhibited intense phosphorylation of a 55-kDa protein that was blocked by ATLa (aspirin-triggered lipoxin) treatment (10 -50 nM) (13). This 55-kDa protein was identified as leukocyte-specific protein 1, a downstream component of the p38-MAPK cascade in neutrophils.…”
mentioning
confidence: 99%